(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
This article explores the gender dimension of the Macedonian political scene, in order to obtain theoretical knowledge about the role and impact of gender balance in governing political structures on the quality of decisions important for everyone in society, directly or indirectly. For this analysis, among others, statistical data was used from the archives of the state and other relevant institutions. The results showed that women remain the underrepresented gender in politics, especially in higher circles, where there is a higher concentration of power and the most important decision-making processes take place. Perhaps one of the most impactful ways to achieve gender balance would be by implementing quotas, and they should be on the government’s agenda, as it remains to be an effective measure and useful tool to achieve gender parity. The quota system, in fact, enabled a high percentage of women in politics and decision-making, with 41.67 % in the Parliament and 36.45 % in the local councils. However, a gender balance of 50/50 has not yet been reached, especially not in the highest positions, where there are no quotas, such as presidents, prime ministers, mayors or ministers. Keywords: gender; gender equality; quota; political engagement.